2009
DOI: 10.1021/cm902674h
|View full text |Cite
|
Sign up to set email alerts
|

Role of Magnesium Ion in the Stabilization of Biogenic Amorphous Calcium Carbonate: A Structure−Function Investigation

Abstract: Magnesium is a key component used by many organisms in biomineralization. One role for magnesium is in stabilizing an otherwise unstable amorphous calcium carbonate (ACC) phase. The way in which this stabilization is achieved is unknown. Here, we address this question by studying the chemical environment around magnesium in biogenic and synthetic ACCs using Mg K-edge X-ray absorption spectroscopy (XAS). We show that although the short-range structure around the Mg ion is different in the various minerals studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
191
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(204 citation statements)
references
References 36 publications
9
191
2
2
Order By: Relevance
“…Indeed, just like calcium, Mg 2+ is a closed shell diamagnetic cation, and magnesium-25, the NMR active isotope, is a spin-5/2 low-nucleus of low natural abundance (~10.0%), [38] with a relatively large quadrupole moment, meaning that the NMR signals can be very broad. Although techniques like 25 Mg solid state NMR [38,39,76,88] and Mg K-edge EXAFS and XANES [89][90][91] are being developed to help investigate the local structure around magnesium, they cannot be used routinely, because they require access to ultra-high field magnets or soft X-ray synchrotron sources. Furthermore, these experiments can be very time-consuming, especially for samples in which the Mg content is low.…”
Section: D Towards the Analysis Of The Local Environment Of The Magmentioning
confidence: 99%
“…Indeed, just like calcium, Mg 2+ is a closed shell diamagnetic cation, and magnesium-25, the NMR active isotope, is a spin-5/2 low-nucleus of low natural abundance (~10.0%), [38] with a relatively large quadrupole moment, meaning that the NMR signals can be very broad. Although techniques like 25 Mg solid state NMR [38,39,76,88] and Mg K-edge EXAFS and XANES [89][90][91] are being developed to help investigate the local structure around magnesium, they cannot be used routinely, because they require access to ultra-high field magnets or soft X-ray synchrotron sources. Furthermore, these experiments can be very time-consuming, especially for samples in which the Mg content is low.…”
Section: D Towards the Analysis Of The Local Environment Of The Magmentioning
confidence: 99%
“…This is in contrast to the calcium and calcium-magnesium carbonate systems, where the transformation of the amorphous precursors at equivalent conditions in solution has been shown to be much faster: the transformation of ACC to crystalline CaCO 3 in solution occurs in 1-2 min at ambient temperature (Ogino et al 1987) and is considered to involve a dehydration process (Rodriguez-Blanco et al 2011a, b). The crystallization of Mg-doped ACC although it occurs at a slower pace compared to ACC (Rodriguez-Blanco et al 2011a, b;Politi et al 2010) it is still much faster than ADC. Furthermore, in the presence of Mg the energy needed to dehydrate the Mg ion is higher compared to the Ca ion (Di Tommaso and de Leeuw 2010).…”
Section: Is Amorphous Dysprosium Carbonate Special?mentioning
confidence: 99%
“…Observation of deposits of ACP indicates that the presence of Mg 2+ is able to stabilize this phase. A very recent study showed that although the short-range structure around the Mg 2+ ion is different in the various minerals studied, they all involve a shortening of the Mg−O bond length, and the compact structure around magnesium introduces distortion in the host mineral, thus inhibiting its crystallization [12]. The apparent stabilization of ACP may be because of the binding of Mg 2+ to newly formed nuclei, not only preventing these from reaching a critical growth size and subsequent Ostwald maturation, but also leading to redissolution [13].…”
Section: Nucleation and Growth Of Calcium Orthophosphate Crystals Fromentioning
confidence: 99%